Influence of Ca[Mg3SiN4]Ce3+ phosphor’s concentration on optical properties of the 5600K RP-WLEDs - Phu Tran Tin; Minh Tran; Tran Thanh Trang (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, we propose Ca[Mg3SiN4]Ce3+ Phosphor as a new material solution for improving the optical properties in terms of CRI, CQS. D-CCT, LO of the 5600K remote-packaging white LEDs (RP-WLEDs). In the first stage, we built and investigated the 5600K RP-WLEDs by adding the red phosphor to the phosphor layer. Then, the scattering processes inside the phosphor layer are investigated by Mat Lab software. From the research results, we discovered that the concentration of the adding phosphor significantly improved the optical properties of the5600K RP-WLEDs. All the results are convinced by Light Tools and Mat Lab software.